Why do Chinese migrant workers return? Exploring economic push-pull factors and emotional ties - Qiong Zhou; Zhe Huang; Lining Zeng; Jun Xu (PLoS ONE, 2025)
Over the past few decades, China’s economic growth and urbanization have driven a significant migration of rural laborers to cities. Recently, however, an increasing number of migrant workers have chosen to return to their hometowns for employment opportunities. Understanding the factors influencing this return migration is crucial but challenging due to the complexity and diversity of these factors and their intricate interrelationships. Moreover, existing research on migrant workers’ return lacks a systematic theoretical framework and comprehensive empirical analysis. To address these gaps, our study utilizes the "Push-Pull Theory" from migration theory to develop a comprehensive model. This model investigates how perceived benefits, trust, costs, and both personal and government support affect migrant workers’ willingness to return. We employ structural equation modeling (SEM) for empirical analysis, revealing that perceived benefits, trust, and costs significantly influence migrant workers’ perception of return support. This perception, in turn, enhances their willingness to return. Additionally, our findings show that government support positively moderates the relationship between perceived benefits and costs with return support. However, it does not significantly affect the relationship between perceived trust and support, indicating that policy incentives alone may not sufficiently build trust in hometowns. Furthermore, emotional factors—such as family and place attachment, community involvement, and quality of life in hometowns—indirectly influence the decision to return by shaping perceived benefits, trust, and costs. This study advances the application of Push-Pull Theory by integrating economic factors with emotional bonds in the context of return migration. It provides novel insights into how both economic incentives and emotional ties drive migrant workers’ decisions to return, offering a more nuanced understanding of migration dynamics in China.